The Potential of "Pelak" as a Science Learning Media at SMP Negeri 5 Kerinci on Plant Diversity Material - Tiara; Wilia, Grasya Putri; Novinovrita; Saputra, Dalli Yulio (Journal of Curriculum and Pedagogic Studies (JCPS), 2024)
Pelak or garden is land owned by the community for planting various kinds of plants which is located not far from the house. Pelak has the potential as a real learning medium. This research aims to find out the types of plants found in Pelak and the potential of Pelak as a science learning medium, especially plant diversity material at SMPN 5 Kerinci. This research uses a qualitative approach. Data was collected through interviews and observations. The resource person for this research is the owner of Pelak and the 7th grade science teacher. Based on the research results, it is known that in Pelak around SMP Negeri 5 Kerinci there are a variety of plants consisting of 9 types of plants. Five of them fall into the monocot group and 4 dicots. Of the several types of plants, the most numerous are the zingiberaceae group. The potential of acting as a learning medium can be seen from the diversity of plants, the close distance to schools, the shady and comfortable atmosphere, the security in the surrounding area which is maintained because it is close to residential areas, the existence of internet access which can support students in obtaining learning information online and The surrounding environment provides opportunities for students to learn directly from real objects.